Was ist die Standardform von y = (2x + 7) (- 3x-3) -4x ^ 2-8x?

Was ist die Standardform von y = (2x + 7) (- 3x-3) -4x ^ 2-8x?
Anonim

Antworten:

# y = -10x ^ 2-35x-21 #

Erläuterung:

Gegeben -

# y = (2x + 7) (- 3x-3) -4x ^ 2-8x #

# y = -6x ^ 2-21x-6x-21-4x ^ 2-8x #

# y = -10x ^ 2-35x-21 #

Erweitern Sie die Klammern

# y = (2x + 7) (- 3x-3) -4x ^ 2-8x #

# => y = -6x ^ 2-6x-21x-21-4x ^ 2-8x #

Sammeln Sie wie Begriffe

# => y = -10x ^ 2-35x-21 #

Nun ist es in der Form # y = ax ^ 2 + bx + c #